Social determinants of health: especial atention to the health of women - Méndez Aristizábal, Inés Dayana (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2015)
A good health care system is indisputable to be an important health determinant. However, more than the previous is needed in order to provide a human being and communities with what health and wellbeing should be. Social and economic factors, such poverty and inequality, can be determinant in what can be understood as good or bad health for communities and individuals. Poverty and inequality have considerable impacts on people´s quality of life and time expectancy. Those factors tend to have a worse impact on women because of their biological characteristics, malnutrition, and on how society has shaped and the role women play in it. Because of the previous an increase on bad health indexes can be observed when one analyzes women health data.